2012
DOI: 10.1007/s10144-012-0349-y
|View full text |Cite
|
Sign up to set email alerts
|

Coupling inter‐patch movement models and landscape graph to assess functional connectivity

Abstract: Landscape connectivity is a key process for the functioning and persistence of spatially-structured populations in fragmented landscapes. Butterflies are particularly sensitive to landscape change and are excellent model organisms to study landscape connectivity. Here, we infer functional connectivity from the assessment of the selection of different landscape elements in a highly fragmented landscape in the Île-de-France region (France). Firstly we measured the butterfly preferences of the Large White butterf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
0
13
0
1
Order By: Relevance
“…Bergerot et al (2012) compared movement patterns for the Speckled Wood (Pararge aegeria) in different landscapes and found that individuals were more sedentary in a highly fragmented urban landscape (Paris) than in other landscape types. The work of Bergerot et al (2013) on the Cabbage White (Pieris brassicae) and that of Leidner and Haddad (2010) on Atrytonopsis spec 1 demonstrate the high mobility of certain butterfly species in highly urbanised landscapes, but also highlight certain natural and human barriers to butterfly movement.…”
Section: Introductionmentioning
confidence: 97%
“…Bergerot et al (2012) compared movement patterns for the Speckled Wood (Pararge aegeria) in different landscapes and found that individuals were more sedentary in a highly fragmented urban landscape (Paris) than in other landscape types. The work of Bergerot et al (2013) on the Cabbage White (Pieris brassicae) and that of Leidner and Haddad (2010) on Atrytonopsis spec 1 demonstrate the high mobility of certain butterfly species in highly urbanised landscapes, but also highlight certain natural and human barriers to butterfly movement.…”
Section: Introductionmentioning
confidence: 97%
“…In the informed mode, decisions are made by an individual of a highly cognitive species (such as a bear, cougar or lion), which has the capability to locally select a route that minimizes the cost for movement (Chetkiewicz and Boyce 2009;Elliot et al 2014). The alternative naïve mode is frequently applied in the context of metapopulation models, to more-or-less randomly moving individuals that rely on chance to make it through dispersal journeys (Bergerot et al 2013). A combination of both strategies will probably apply to many organisms, in particular to terrestrial organisms with low dispersal capabilities such as amphibians (Brown et al 2014;Campbell Grant et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The persistence of many species in mosaic landscapes depends on the capacity of species to move and disperse within a network of suitable patches (Nathan et al 2008;Bergerot et al 2012). In this context, butterflies are useful model organisms (Watt and Boggs 2003) because of their relatively short life cycles, their quick responses to environmental change (Erhardt 1985;Warren and Bourn 2011), and because they are relatively well-studied (Stevens et al 2010).…”
Section: Introductionmentioning
confidence: 99%